2014
DOI: 10.1128/iai.02256-14
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Bacterial Species Associated with Endodontic Infection Evade Innate Immune Control by Disabling Neutrophils

Abstract: dEndodontic infections, in which oral bacteria access the tooth pulp chamber, are common and do not resolve once established. To investigate the effects of these infections on the innate immune response, we established a mouse subcutaneous chamber model, where a mixture of four oral pathogens commonly associated with these infections (endodontic pathogens [EP]), i.e., Fusobacterium nucleatum, Streptococcus intermedius, Parvimonas micra, and Prevotella intermedia, was inoculated into subcutaneously implanted ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 58 publications
(62 reference statements)
0
37
0
Order By: Relevance
“…Species heterogeneity also underlines the need to continue in‐depth metagenomic characterization of the microbiota in inflammatory disease to reveal disease‐modulating properties. Intriguingly, some Prevotella species could have evolved immune escape mechanisms, including induction of neutrophil dysfunction,, that may lead to chronic inflammation due to defective clearance. Deciphering the genetic and mechanistic basis of immune escape by Prevotella may in the future reveal disease‐modifying drug targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species heterogeneity also underlines the need to continue in‐depth metagenomic characterization of the microbiota in inflammatory disease to reveal disease‐modulating properties. Intriguingly, some Prevotella species could have evolved immune escape mechanisms, including induction of neutrophil dysfunction,, that may lead to chronic inflammation due to defective clearance. Deciphering the genetic and mechanistic basis of immune escape by Prevotella may in the future reveal disease‐modifying drug targets.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies using human monocyte‐derived dendritic cells, odontoblast‐like cell clones and a gingival epithelial cell line suggest that Prevotella exhibit an enhanced capacity to induce inflammatory mediators [IL‐6, IL‐8 and tumour necrosis factor‐ α (TNF‐ α )] when compared with strict commensal oral bacteria and even P. gingivalis . Interestingly, a murine study using a subcutaneous chamber model found that oral commensal Streptococcus mitis infection could readily be cleared, whereas infection with Prevotella intermedia was uncontrolled for more than 7 days . The Prevotella intermedia infection was found to induce increased host cell infiltration compared with S. mitis ; however the infiltrating neutrophils were defective in terms of phagocytosis and reactive oxygen species production, and exhibited a necrotic morphology.…”
Section: Periodontitismentioning
confidence: 99%
“…32 It is important to note that previous studies have identified P. intermedia in the respiratory tract in association with chronic bronchitis, 33 pneumococcal pneumonia, 34 and pulmonary infections in the context of cystic fibrosis. 39 While it has been suggested that P. intermedia can precede and favor the colonization of red complex bacteria in the pulmonary environment, a study found that Prevotella spp. 27 Some MMPs are also notably present in asthma, such as MMP-1, MMP-2, MMP-3, MMP-8, and MMP-9, which are highly expressed in allergic and asthmatic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…polymorphum decreased neutrophil viability but increased apoptosis, suggesting that this strain may be critical in reducing defensive functions of neutrophils during initiation of disease. In a recent study, Matsui et al 47 reported details of oral pathogens with a combination of F. nucleatum , Streptococcus intermedius , Parvimonas micra , and Prevotella intermedia and how they impact neutrophil function in a mouse chamber model. Although the focus of this study and the current study is considerably different, data support findings of this in vivo study and advance the field to comparison of three strains of F. nucleatum , suggesting a difference between strains of F. nucleatum and their actions on neutrophils.…”
Section: Discussionmentioning
confidence: 99%